In vitro and non‐invasive in vivo effects of the cannabinoid‐1 receptor agonist AM841 on gastrointestinal motor function in the rat. Issue 12 (20th September 2015) - Abalo, R.; Chen, C.; Vera, G.; Fichna, J.; Thakur, G. A.; López‐Pérez, A. E.; Makriyannis, A.; Martín‐Fontelles, M. I.; Storr, M.
Abstract: Background: Cannabinoids have been traditionally used for the treatment of gastrointestinal (GI) symptoms, but the associated central effects, through cannabinoid‐1 receptors (CB1R), constitute an important drawback. Our aims were to characterize the effects of the recently developed highly potent long‐acting megagonist AM841 on GI motor function and to determine its central effects in rats. Methods: Male Wistar rats were used for in vitro and in vivo studies. The effect of AM841 was tested on electrically induced twitch contractions of GI preparations ( in vitro ) and on GI motility measured radiographically after contrast administration ( in vivo ). Central effects of AM841 were evaluated using the cannabinoid tetrad. The non‐selective cannabinoid agonist WIN 55, 212‐2 (WIN) was used for comparison. The CB1R (AM251) and CB2R (AM630) antagonists were used to characterize cannabinoid receptor‐mediated effects of AM841. Key Results: AM841 dose‐dependently reduced in vitro contractile activity of rat GI preparations via CB1R, but not CB2R or opioid receptors. In vivo, AM841 acutely and potently reduced gastric emptying and intestinal transit in a dose‐dependent and AM251‐sensitive manner. The in vivo GI effects of AM841 at 0.1 mg/kg were comparable to those induced by WIN at 5 mg/kg. However, at this dose, AM841 did not induce any sign of the cannabinoid tetrad, whereas WIN induced significant central effects. Conclusions & Inferences: The CB1R megagonist AM841 may potently depress GI motor function in the absence of central effects. This effect may be mediated peripherally and may be useful in the treatment of GI motility disorders. Abstract : AM841, a new cannabinoid agonist, dose‐dependently depressed gastrointestinal motor function in the rat, both in vitro (organ bath experiments) and in vivo (non‐invasive radiographic analysis), through the activation of CB1, but not CB2 cannabinoid receptors. The effect was relatively short‐lasting in spite of the fact that this megagonist binds to its receptor in a covalent manner. Central effects (analgesia, hypothermia, catalepsia, and hypo locomotion) were absent at a dose that potently depressed gastrointestinal motility.